Implementations of Interactive discussions with customers to put incentives and increasing of sales along with brand loyalty - Al Mehdi, Abdullah (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.